Susceptibility to apoptosis is differentially regulated by c-myc and mutated Ha-ras oncogenes and is associated with endonuclease availability. - Arends, M. J. (Nature Publishing Group, 1993)
Oncogenes and oncosuppressors can deregulate cell replication in tumours, and recently have been shown to influence the probability of apoptosis. The effects of human c-myc and mutated (T24) Ha-ras oncogenes on susceptibility to apoptosis were investigated by introducing them into immortalised rat fibroblasts. The resulting family of transfectants showed closely similar measures of proliferation, but widely divergent rates of apoptosis, differing by up to fifteen-fold, that correlated inversely with population expansion rates in vitro. T24-ras transfectants with moderate or high p21ras expression showed reduced apoptosis, and this was reversed by pharmacological inhibition of membrane localisation of p21ras by mevinolin. In contrast, c-myc stimulated apoptosis, and this was further enhanced by serum deprivation. Inducibility of effector proteins represents one possible mechanism of genetic control of the susceptibility to apoptosis, and its investigation showed that c-myc was associated with expression by viable cells of latent calcium/magnesium sensitive endonuclease activity characteristic of apoptosis. In contrast, endonuclease activity was not detected in viable cells of a T24-ras transfectant expressing high levels of p21ras. Thus, there appeared to be differential regulation of susceptibility to apoptosis, positively by c-myc and negatively by activated ras, and this was associated with availability of endonuclease activity. Genetic modulation of apoptosis in human neoplasms is likely to influence net growth rate, retention of cells acquiring new mutations and response to certain chemotherapeutic agents. IMAGES: